On Pluralism within Community - Faust, Don (JOMANTARA, 2025)
Although it is most usual to study the shared characteristics of community members, in this paper we instead emphasize the pluralism within a community. The framework within which we will proceed is Explorationism, a perspective that all our knowledge is (so far) less than certain, that all our knowledge is indeed (so far) only partial and only tentative. This perspective will help us better elucidate how pluralism in every community contributes to the community’s vitality and success.